LEGAL POSITION OF SONG COPYRIGHT AS AN OBJECT OF DEBT GUARANTEE IN A FINANCING SCHEME BASED ON INTELLECTUAL PROPERTY - Devi Febriyanti; Rehnalemken Ginting; Waluyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
.